2002
DOI: 10.4319/lo.2002.47.4.0967
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for facilitated uptake of Hg(II) by Vibrio anguillarum and Escherichia coli under anaerobic and aerobic conditions

Abstract: A mer-lux bioreporter was used to study uptake of inorganic mercury, Hg(II), at trace concentrations by two facultatively anaerobic bacterial species, Vibrio anguillarum and Escherichia coli. Uptake of Hg(II) by these bacteria appeared to be facilitated, rather than by passive diffusion. Three lines of evidence support this conclusion. First, under anaerobic conditions Hg(II) uptake was greatly decreased compared with aerobic conditions, even though the chemical composition of the medium was identical except f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(128 citation statements)
references
References 31 publications
7
117
4
Order By: Relevance
“…The uptakerate exhibited a log-log relationship with the dissolved concentration for both Hg species, indicating that uptake was primarily a Freundlich absorption type dominated by passive diffusion or a facilitated transport process (Golding et al 2002). Whether the dissolved uptake is active, however, cannot be concluded from this study.…”
Section: Discussioncontrasting
confidence: 45%
“…The uptakerate exhibited a log-log relationship with the dissolved concentration for both Hg species, indicating that uptake was primarily a Freundlich absorption type dominated by passive diffusion or a facilitated transport process (Golding et al 2002). Whether the dissolved uptake is active, however, cannot be concluded from this study.…”
Section: Discussioncontrasting
confidence: 45%
“…Bacterial mercuric reductase may be active under these conditions but with very low efficiencies (Golding et al 2002;Schaefer et al 2002). Also, humic substances may induce DGM pro- duction (Allard and Arsenie 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Mortazavi et al (2005) studied the effect of pH on the efficiency of removal of HgCl 2 by a P. putida strain. Other studies have indicated that pH is an important factor that significantly affects the concentration of bioavailable mercury, higher concentrations of mercury accumulating in the bacteria with the decreasing of pH (Golding et al 2002;Kelly et al 2003;Golding et al 2008;Ahn et al 2010). However, until now, the effect of pH on the expression of merA at the transcriptional level, an important process during mercury transformation, has not been examined.…”
Section: Introductionmentioning
confidence: 98%